KOMUNIKASI BUDAYA PENGGUNAAN BAHASA CAMPUR KODE PADA GENERASI MILENIAL JAKARTA - Rizka, Layinuvar Anggia; Tanuwidjaja, Ferdinand Fransiskus; Wijaya, Linda (Universitas Teuku Umar, 2021)
The mixing code language between Bahasa and English as daily conversations in the millennial generation has a massive use nowadays. In this research, the background of that phenomenon will be analyzed by the accommodation communication theory approach. The objective of this research is to observe the accommodation process of this type of communication and how millennials habituate it to any other communications and interactions. The method of this research is qualitative descriptive. The informants will be chosen by using purposive sampling. The data is collected by interviews, direct observations, and documentation. The data analyzing technique in this research will be carried through several steps; data reduction, data presentation, and conclusion. The research result showed that the usage of the mixing code allowed by positive interpretations of English as a modern language than Bahasa. Pride and prestige of social status for its speaker also motivate millennials to speak it. Therefore, a lot of millennials try to fluent in English by mixing it with Bahasa in their daily conversation and try to adjust to those social perspectives. Thus, the process of accommodation of this mixing code communication takes place easier in millennial circles.